From molecules to medicine: a systematic review of Gastrodia elata’s bioactive metabolites and therapeutic potential - Zhou, Xiantai; Han, Minna; Yan, Shiyu; Wang, Mengyuan; Zu, Shengzhou; Zhong, Shenghui (Frontiers in Pharmacology, 2025)
The dried tuber of Gastrodia elata (GE), a perennial orchid with a 2,200-year medicinal history documented in the Shennong Bencaojing (200 BCE), remains a cornerstone of traditional Chinese medicine (TCM) and contemporary integrative therapies across Asia. Initially prescribed for neurological disorders (e.g., epilepsy, stroke prophylaxis) and hypertension, modern research has expanded its therapeutic portfolio to include anti-aging, antitumor, and osteoprotective applications. This systematic review synthesizes 1) traditional ethnopharmacological uses, 2) phytochemical profiling of 100+ identified bioactive metabolites (e.g., gastrodin, parishins), and 3) mechanistic insights into their pharmacokinetic behaviors and pharmacodynamic actions. Notably, botanical drug interactions in TCM formulations enhance gastrodin’s blood-brain barrier penetration, elucidating clinical efficacy. While in vitro/vivo studies validate GE’s antioxidant and neuroprotective effects, translational challenges persist: 1) Limited clinical trials on novel indications (e.g., osteoporosis); 2) Unclear structure-activity relationships of minor metabolites; 3) Standardization needs for industrial applications. This work provides an evidence base to guide future research on GE’s diversified therapeutic development.